Re-layout Gudang dan Standarisasi Penamaan Part Ex-Project di PT. Djarum - Christian Ardy Purnama; Herry Christian Palit (Jurnal Titra, 2023)
The main focus on the existing work process in the Engineering section of PT.Djarum is the fulfilment of projects originating from related users. With this project fulfilment request, certain resources are needed, one of which is parts. The parts used are common parts that can help in the process of making a part of the project. After a project is completed, there are some parts left over from the project and must be stored again. These parts are referred to as ex-project parts. The process of storing ex-project parts is still not well done, where there are obstacles in administration, especially naming each part. In addition, there are shortcomings when the part will be stored in the shelf, namely the arrangement of the part into the shelf. Due to this, engineer PT Djarum has a project, which is moving the storage to a new warehouse. In this new warehouse, it is desired that the administration process or part arrangement can run well. To answer this desire, the ABC method is used in the process of arranging parts on shelves. By using this method, classification and grouping of parts are obtained based on the frequency of movement of the parts in the warehouse. The classification and grouping are based on the cumulativepercentage value of each part. By knowing this information, there are considerations in the arrangement of parts so that the search and administration process can run better.